Childhood Trauma as a Cause of Psychosis: Linking Genes, Psychology, and Biology. (January 2013) - van Winkel, Ruud; van Nierop, Martine; Myin-Germeys, Inez; van Os, Jim
Recent studies have provided robust evidence for an association between childhood trauma (CT) and psychosis. Meta-analyses have quantified the association, pointing to odds ratios in the order of around 3, and prospective studies have shown that reverse causation is unlikely to explain the association. However, more work is needed to address the possibility of a gene–environment correlation, that is, whether genetic risk for psychosis predicts exposure to CT. Nevertheless, multiple studies have convincingly shown that the association between CT and psychosis remains strong and significant when controlling for genetic risk, in agreement with a possible causal association. In addition, several studies have shown plausible psychological and neurobiological mechanisms linking adverse experiences to psychosis, including induction of social defeat and reduced self-value, sensitization of the mesolimbic dopamine system, changes in the stress and immune system, and concomitant changes in stress-related brain structures, such as the hippocampus and the amygdala, findings that should be integrated, however, in more complex models of vulnerability. It is currently unclear whether genetic vulnerability plays a role in conferring the mental consequences of adversity, and which genes are likely to be involved. The current, limited evidence points to genes that are not specifically involved in psychosis but more generally in regulating mood (serotonin transporter gene), neuroplasticity (brain-derived neurotrophic factor), and the stress-response system ( FKBP5 ), in line with a general effect of CT on a range of mental disorders, rather than suggesting specificity for psychosis.